Association between combinations of genetic polymorphisms and epidemiopathogenic forms of bovine paratuberculosis. Issue 2 (February 2018) - Juste, Ramon A.; Vazquez, Patricia; Ruiz-Larrañaga, Otsanda; Iriondo, Mikel; Manzano, Carmen; Agirre, Mikel; Estonba, Andone; Geijo, Maria V.; Molina, Elena; Sevilla, Iker A.; Alonso-Hearn, Marta; Gomez, Nieves; et al.
Abstract: Control of major mycobacterial diseases affecting livestock is a challenging issue that requires different approaches. The use of genetic markers for improving resistance to Mycobacterium avium subsp. paratuberculosis infection in cattle has been explored as a promising population strategy We performed paratuberculosis epidemiopathogenic phenotypic and genotypic characterization involving 24 SNPs in six candidate genes ( NOD2, CD209, SLC11A1, SP110, TLR2 and TLR4 ) on 502 slaughtered Friesian cows. In the current study, we investigate whether recently proposed paratuberculosis (PTB) epidemiopathogenic (EP) forms (apparently free-AF, latent-LAT and patent-PAT) could be associated with some combination of these 24 SNPs. Best EP form grouping was obtained using a combination of 5 SNPs in four genes ( CD209 : rs210748127; SLC11A1 : rs110090506; SP110 : rs136859213 and rs110480812; and TLR2 : rs41830058). These groups were defined according to the level of infection progression risk to patent epidemiopathogenic forms and showed the following distributions: LOWIN (low) with 39 (8%) cases (94.9% AF/5.1% LAT/0% PAT); LATIN (low) with 17 (3%) cases (5.9% AF/94.1% LAT/0% PAT); AVERIN (average) with 413 (82%) cases (52.1% AF/38.5% LAT/9.4% PAT) and PATIN (patent) with 33 (7%) cases (36.4% AF/24.2% LAT/39.4% PAT). Age of slaughter was significantly higher for LATIN (88.3 months) compared to AVERIN (65.3 months; p = 0.0007) and PATIN (59.1 months; p = 0.0004), and for LOWIN (73.9 months) compared to PATIN (p = 0.0233), and nearly significant compared to AVERIN (p = 0.0572) These results suggest that some selected genetic polymorphisms have a potential use as markers of PTB EP forms and thus add a new tool for the control of this widespread infection.